The golden child [videorecording (DVD)] - Ritchie, Michael, 1938-2001; Murphy, Eddie, 1961-; Lewis, Charlotte, 1967-; Dance, Charles; Reate, J. J.; Wong, Victor; Cobb, Randall, 1950-; Hong, James; Chen, Shakti, 1958-; Feldman, Edward S., 1929-2020; Wachs, Robert D.; Feldman, Dennis (Widescreen DVD collection., 2017)
Murphy goes to the rescue of a child with mystical powers who has been abducted by an evil cult.